The Arabic manuscript tradition : a glossary of technical terms and bibliography - Gacek, Adam. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2001)
Covering the entire spectrum of Arabic manuscripts, and especially the handwritten book, this book consists of a glossary of technical terms and a bibliography. The technical terms, collected from a variety of sources, embrace a vast range of topics dealing with the making and reading (studying) of Arabic manuscripts. They include: the Arabic scripts, penmanship, writing materials and implements, the make-up of the codex, copying and correction, decoration and bookbinding. A similar coverage is reflected in the bibliography. In view of the fact that, as yet, there is no concise monograph on Arabic manuscripts in the English language, this book is an important contribution to this field. And, since Arabic manuscripts represent an enormous resource for research, this work is an indispensable reference for all students of Islamic civilization.